THE EFFECT OF MANAGEMENT INFORMATION SYSTEM AND KNOWLEDGE MANAGEMENT ON MSME PERFORMANCE MEDIATED BY ORGANIZATIONAL COMMITMENT IN MAJALENGKA MSMEs - Suyanto Suyanto; Kusnadi Kusnadi; Willy Arafah (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2021)
The purpose of this study was to investigate the Effect of Management Information System and Knowledge Management on MSME Performance mediated by Organizational Commitment to MSMEs in Majalengka. The methodology used in this study is causality hypothetical testing using cross sectional, hypothesis testing is a method of decision making based on data analysis from controlled and uncontrolled experiments on SMEs in Majalengka. The population is 6,376 people with a sample of 377 respondents. Data collection using questionnaires and data analysis techniques using Path Analysis and PLS The model proposed in this study shows the direct and indirect effect of Management Information System and Knowledge Management on MSME Performance Mediated by Organizational Commitment. Future research should study other variables that influence the influence of UMKM Performance such as marketing, access to capital, entrepreneurial abilities, human resources, financial knowledge and business plans. This research shows that Management Information System and Knowledge Management as well as Organizational Commitment affect MSME Performance either directly or indirectly. This research is a useful tool to improve MSME Performance through improving Management Information System and Knowledge Management as well as Organizational Commitment. This research model purifies the overall understanding that there is a direct and indirect influence of the Management Information System and Knowledge Management on MSME Performance mediated by Organizational Commitment